Reinterpretasi Konsep Qawwamah dalam Nafkah Keluarga Modern - Muhammad Siddieq Al'Amin; Navila Ash Shofwa Kamila Farid; Muhammad Roziqur Rijal Fathony; Salma Farahin Sania (Al-Kindi, 2026)
This study examines the reinterpretation of the concept of qawwamah in the context of Muslim family finances in modern times. Through a hermeneutic-contextual approach and interpretive analysis, this study explores how the concept of qawwamah in QS. An-Nisa: 34 can be understood in a more equitable and relevant manner to contemporary social realities. The research uses library research methods with qualitative-normative approaches, analyzing classical to contemporary interpretations. The findings show that qawwamah is conditional and functional, rather than absolute and hierarchical. A reinterpretation based on maqashid syariah offers an understanding of qawwamah as collaborative leadership that recognizes women's economic contributions and emphasizes shared responsibility within the family. This study contributes to the development of Islamic family law that is gender-responsive and in line with the principles of Islamic justice.